Clinical experience with insulin detemir, biphasic insulin aspart and insulin aspart in people with type 2 diabetes: Results from the Kuwait cohort of the A 1 chieve study - Alaa Daban; Hussain Haji Ali (Indian Journal of Endocrinology and Metabolism, 2013)
Background: The A 1 chieve, a multicentric (28 countries), 24-week, non-interventional study evaluated the safety and effectiveness of insulin detemir, biphasic insulin aspart and insulin aspart in people with T2DM (n = 66,726) in routine clinical care across four continents. Materials and Methods: Data was collected at baseline, at 12 weeks and at 24 weeks. This short communication presents the results for patients enrolled from Kuwait. Results: A total of 1185 patients were enrolled in the study. Four different insulin analogue regimens were used in the study. Study patients had started on or were switched to biphasic insulin aspart (n = 472), insulin detemir (n = 472), insulin aspart (n = 4), basal insulin plus insulin aspart (n = 188) and other insulin combinations (n = 48). At baseline, glycaemic control was poor for both insulin naïve (mean HbA 1 c: 9.8%) and insulin user (mean HbA 1 c: 9.4%) groups. After 24 weeks of treatment, both the groups showed improvement in HbA 1 c (insulin naïve: −2.4%, insulin users: −1.7%). No major hypoglycaemic episodes were observed at 24 weeks. SADR was reported in 0.1% of insulin users. Conclusion: Starting or switching to insulin analogues was associated with improvement in glycaemic control with a low rate of hypoglycaemia.